The Complexity of Radicalization and Recruitment in Kwale, Kenya - Mkutu, Kennedy (Terrorism and political violence, 2021)
Al-Shabaab, the East-African affiliate of Al Qaeda has carried out a number of large-scale devastating attacks in the region and a steady stream of smaller scale ones. In recent years Al-Shabaab’s ongoing strength has relied upon its ability to build local support within Kenya. This work looks at Kwale County on Kenya’s coast and examines some of the factors involved in radicalization and/or recruitment into the group, including economic hardship, historical marginalization, land injustices, drugs, problems at the family level and poor relationships with state security agencies. It highlights the more recent phenomenon of those returning from fighting with Al-Shabaab and the problems of their reintegration. It concludes that there are a number of phenomenon related in complex and sometimes self-perpetuating ways which all need to be considered in the response to radicalization and recruitment.